Prevalence of Thai People with Lumbar Instability and Associated Factors: A Cross-Sectional Study - Chatprem T; Puntumetakul R; Siritaratiwat W; Hunsawong T; Boucaut R (Journal of Pain Research, 2022)
Thiwaphon Chatprem,1,2 Rungthip Puntumetakul,1,2 Wantana Siritaratiwat,1,2 Torkamol Hunsawong,1,2 Rose Boucaut3 1School of Physical Therapy, Faculty of Associated Medical Sciences, Khon Kaen University, Khon Kaen, Thailand; 2Research Center in Back, Neck, Other Joint Pain and Human Performance (BNOJPH), Faculty of Associated Medical Sciences, Khon Kaen University, Khon Kaen, Thailand; 3International Centre for Allied Health Evidence; University of South Australia, Allied Health and Human Performance, Adelaide, AustraliaCorrespondence: Rungthip Puntumetakul, Research Center in Back, Neck, Other Joint Pain and Human Performance (BNOJPH), Faculty of Associated Medical Sciences, Khon Kaen University, Khon Kaen, Thailand, Tel +66 83 419 6186, Email rungthiprt@gmail.comBackground: Lumbar instability has been extensively reported; however, the risk factors for lumbar instability remain poorly defined, and understanding this condition better would help health professionals and their patients.Proposal: To determine the prevalence of lumbar instability in Thai people with chronic low back pain (CLBP) and explore the factors associated with lumbar instability in these patients.Patients and Methods: Using multistage random sampling methods, 1762 participants with CLBP were enrolled in the study from six regions of Thailand. Data were collected using a paper-based questionnaire. Participants were interviewed by physical therapists in the hospital they attended. They were classified as having lumbar instability when they attained ≥ 7/14 items on the lumbar instability screening tool. Univariate and multivariate regression analysese were used to determine the possible factors associated with lumbar instability.Results: There were 961 (54.54%) participants with lumbar instability and 801 (45.46%) participants without. The eight factors associated with lumbar instability were: (i) age ≥ 40 years (AOR: 1.36; 95% CI: 1.09– 1.69); (ii) body mass index ≥ 25 kg/m2 (AOR: 1.42; 95% CI: 1.16– 1.74); (iii) having an underlying disease (AOR: 1.32; 95% CI: 1.06– 1.65); (iv) frequent lifting ≥ 5 kg in occupational habits (AOR: 1.69; 95% CI: 1.36– 2.09); (v) prolonged walking ≥ 4 hours per day (AOR: 1.31; 95% CI: 1.04– 1.64); (vi) gardening in leisure time (AOR: 1.37; 95% CI: 1.10– 1.71); (vii) other area of pain (AOR: 1.24; 95% CI: 1.01– 2.52): and (viii) other area of numbness (AOR: 1.85; 95% CI: 1.50– 2.27). When considering only women, prior pregnancy was associated with lumbar instability with OR of 1.76 (95% CI: 1.36– 2.22), p-value < 0.0001.Conclusion: When treating patients with CLBP who are suspected to have lumbar instability, healthcare professionals should consider associated factors that might be modifiable targets for interventions to improve outcomes.Keywords: having an underlying disease, frequent lifting, prolonged walking, other area of pain or numbness, gardening in leisure time